10 Years Soweto. Exhibition - Children and Youth in the Struggle against Apartheid - Grosz, Josef; International Union of Socialist Youth (IUSY), Bonn; African National Congress (1986)
Bemerkungen: Eindruckplakat ohne Eindruck